Improving health professional education and practice through technology : proceedings of a workshop - Cuff, Patricia A. (National Academies Press, 2018)
A pressing challenge in the modern health care system is the gap between education and clinical practice. Emerging technologies have the potential to bridge this gap by creating the kind of team-based learning environments and clinical approaches that are increasingly necessary in the modern health care system both in the United States and around the world. To explore these technologies and their potential for improving education and practice, the National Academies of Sciences, Engineering, and Medicine hosted a workshop in November 2017. Participants explored effective use of technologies as tools for bridging identified gaps within and between health professions education and practice in order to optimize learning, performance and access in high-, middle-, and low-income areas while ensuring the well-being of the formal and informal health workforce. This publication summarizes the presentations and discussions from the workshop.